2011
DOI: 10.1007/s12562-011-0411-2
|View full text |Cite
|
Sign up to set email alerts
|

Adverse and beneficial effects of long-term high-concentration ascorbic acid supplementation in rainbow trout Oncorhynchus mykiss

Abstract: The present study examined the effects of highconcentration ascorbic acid (AsA) supplementation over a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The hypocholesterolemic effect of AA is well documented in terrestrial vertebrates and humans (Ashor, Siervo, van der Velde, Willis, & Mathers, ; Hemilä, ; McRae, ). However, the regulating effect on serum TC level in fish by dietary AA supplementation is contradictory (Ishikawa, Mano, Nakanishi, & Hirose, ; John, George, Hilton, & Slinger, ; Trenzado, Morales, & de la Higuera, ). The present study showed that dietary supplementation with 0.2‒0.4 g/kg l ‐ascorbate‐2‐polyphosphate increased the serum TC level in rainbow trout.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypocholesterolemic effect of AA is well documented in terrestrial vertebrates and humans (Ashor, Siervo, van der Velde, Willis, & Mathers, ; Hemilä, ; McRae, ). However, the regulating effect on serum TC level in fish by dietary AA supplementation is contradictory (Ishikawa, Mano, Nakanishi, & Hirose, ; John, George, Hilton, & Slinger, ; Trenzado, Morales, & de la Higuera, ). The present study showed that dietary supplementation with 0.2‒0.4 g/kg l ‐ascorbate‐2‐polyphosphate increased the serum TC level in rainbow trout.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, dietary AA inclusion significantly depressed the plasma TC level in rainbow trout (John et al, ), Japanese parrot Oplegnathus fasciatus (Ishibashi et al, ) and red sea bream Pagrus major (Hossain et al, ; Ren et al, ). However, most studies demonstrated that the blood TC level of fish is independent of dietary AA levels (El Basuini et al, ; Dawood et al, , ; Gao et al, ; Ishikawa et al, ; Liang et al, ; Ming et al, ; Shahkar et al, ). Thus, the relationship between dietary AA status and steroidogenesis is still unclear in fish, and further studies to identify the reasons for the difference and determine the mechanisms in which dietary AA regulate cholesterol metabolism in fish are needed.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a lack of knowledge of the correlation between immunostimulants and mucosal tissues in fish. Therefore, we treated the fish with high-concentration AsA and LF, which had been confirmed to improve stress resistance and survival in the face of viral and bacterial infections [ [16] , [17] , [18] , [30] ]. For example, it has been reported that Asian catfish showed an increment in resistance to Aeromonas hydrophila upon feeding a diet supplemented with 100 mg LF/kg diet for 7days[17].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental diets (0, 500, 1000, 2000, 5000, or 10,000 mg AsA and 0, 100, or 1000 LF equivalent/kg diet, designated AsA0, AsA500, AsA1000, AsA2000, AsA5000, AsA10,000 and LF0, LF100, LF1000, respectively) were prepared by mixing the commercial diet and distilled water containing AsA or LF at the relevant concentration and stored at –20 °C. The AsA contents of the experimental diets was analyzed by high-performance liquid chromatography following a previous study [ [15] , [16] ] are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation